Defining breeding goals and breeding strategies for chicken production systems in Africa - Peters, S.O.; Ozoje, M.O.; Adenaike, A.S.; Touko, B.A.H.; Tiambo, Christian K.; Adeleke, M.A.; Opoola, O.; Dessie, Tadelle (Springer, 2025)
This chapter defines breeding goals and strategies for chicken production systems in Africa. Sections 18.1 and 18.2 introduces this chapter and highlight types of breeding goals at different trait levels, and critical components for breeding goals in different input systems of production. Sections 18.3 and 18.4 cover traits of economic importance with examples of various breeding programs for low-input systems (e.g., in Ethiopia as an example). Breeding objectives and strategies for adaptability and resilience for optimal productivity in low-input systems are covered in Sects. 18.5 and 18.6. Furthermore, the current practices for chicken breeding systems and the opportunities for the incorporation of omics technologies are discussed in Sects. 18.7 and 18.8. Also, strategic approaches toward integrating environmental, structural, and socioeconomic factors for chicken production to ensure effective multiplication, distribution, and delivery of improved chicken strains to end-users are extensively covered in Sect. 18.9. Lastly, a conclusion and future perspectives are presented in the last part of Sect. 18.9. Several attempts made to develop poultry production and productivity in Africa have concentrated on the introduction of exotic birds, improving management systems, and disease management through vaccination among others. These strategies only contributed marginally to the increase in overall productivity among the exotic-indigenous chicken crossbreds which could not be sustained because of several environmental stressors. Indigenous chickens are crucial components of the sustainability of the African poultry industry. Selection pressure in African indigenous chickens is different compared to introduced exotic commercial breeds because selection footprint is associated with adaptation to local prevailing environmental conditions. Balancing characteristics related to growth with that of reproduction is a vital consideration in the development of African indigenous chicken breeds. In some traits, unfavorable genetic correlations, also called genetic antagonisms, cause a decrease in genetic merit when single-trait selection is practiced. In the same way, failure to consider selection response in correlated traits not directly under selection when selection is practiced also decreases genetic merit. The ability of improved chicken strains to thrive and benefit farmers in harsh environments serves as a success indicator to breeders in Africa. Indigenous and tropically adapted breeds were not given due attention until recently when the African Chicken Genetic Gains (ACGG) group (also recently known as Tropical Poultry Genetic Solutions; TPGS) encouraged the selection and use of indigenous chicken strains with high productivity in semi-scavenging systems in the tropics. Genomic selection is considered the most appropriate standard breeding method in livestock. It is particularly advantageous as it can be used for the selection of breeding animals at an early stage of life without reference to their own breeding or production records. The developments in omics technologies also made the estimations of breeding values (BVs) more accurate, increasing genetic gain by aiding in the selection of genetically superior, disease-free animals at an early stage of life for enhanced productivity and profitability.